Shared Care and Mothers' Post-separation Economic Wellbeing in Finland and Wisconsin, US : Does Child Support and Sharing Child's Costs Matter? - Haapanen, Mari (Springer Nature, 2025)
Children's post-separation living arrangements may have important implications for mothers' economic wellbeing. This study examines self-reported economic wellbeing of mothers with shared versus sole physical custody (also known as shared care) of the child six or more years since separation, using unique survey data on separated parents in Finland (n = 850) and Wisconsin, US (n = 395) in 2019-2020. We use sequential logistic regression models to examine the pathways through which this association potentially occurs-child support and sharing of children's expenses between parents-and whether the outcomes differ by the family policy contexts of Finland and Wisconsin. Our findings suggest that Wisconsin mothers in shared versus sole physical custody arrangements have significantly lower levels of economic hardship, that are fully explained by greater cost-sharing with the other parent of the child. No such relationship is evident in Finland, although cost-sharing is independently negatively associated with economic hardship of Finnish mothers. Findings highlight how fathers' contributions as tied to children's living arrangements matter for post-separation economic wellbeing of mothers, and have implications for shared physical custody and child support policy.